Conflict Management Approaches For Addressing Student Misconduct: A Case Study At MTS Satu Atap Datok Sulaiman Palopo - Darma Wulan; Muhammad Guntur; Rifa'ah Mahmudah Bulu (International Journal of Technology and Education Research, 2026)
Student misconduct remains a significant challenge in educational institutions because it may trigger interpersonal conflicts, disrupt the learning process, and create an unconducive school environment. This study aims to identify the forms of student misconduct that trigger conflicts, analyze the implementation of conflict management approaches, and examine the supporting and inhibiting factors affecting their implementation at MTs Satu Atap Datok Sulaiman Palopo. A qualitative approach with a case study design was employed. Data were collected through interviews, observations, and documentation involving the principal, vice principal for student affairs, teachers, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the dominant forms of student misconduct include truancy, smoking, bullying, and fighting, with verbal bullying identified as the primary trigger of conflict. Conflict management is implemented through preventive, conflict resolution, and restorative approaches supported by collaboration among school stakeholders, continuous communication, and regular evaluation. However, limited parental involvement, peer influence, and students behavioral characteristics remain major challenges. The study concludes that integrating these three approaches contributes to reducing student misconduct, resolving conflicts constructively, and fostering a safer, more disciplined, and conducive learning environment. Keywords: Conflict Management, Student Misconduct, Islamic School, Preventive Approach, Conflict Resolution Approach, Restorative Approach.